PERLAKUAN AUDIT PIUTANG USAHA DALAM MENGIDENTIFIKASI RISIKO PIUTANG TAK TERTAGIH PADA PT GOP OLEH KAP BUDIANDRU & REKAN CABANG SEMARANG - Athaya Anggun Luthfia; Ayunda Putri Nilasari (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
Accounts receivable is a part of current assets that appears on the balance sheet and is a key element in a company’s financial statements. Accounts receivable arises when goods or services are sold on credit. Effective management of accounts receivable is crucial for the sustainability and financial health of a company, as uncollectible receivables can affect liquidity and profitability. This study discusses the process of auditing accounts receivable, starting from engagement, planning, execution of testing, to the reporting of audit results. The method used by the author is qualitative descriptive with data obtained through interviews, documentation, and observation. The results of the audit indicate the existence of uncollectible receivables for three years in the audited company, highlighting the importance of good receivables management and the implementation of effective write-off policies for bad debts.